Afectividad y cognición (verbal) en Darlo todo y no dar nada de Calderón y Los empeños de una casa de Sor Juana - Christopher F. Laferl (E-Spania)
The findings of Performance Studies over the last two decades have rightly highlighted the importance of the regulation of affects in Early Modern Theatre. The production of meaning through words has thus been decentered. In this article, an analysis of two Baroque plays (Darlo todo y no dar nada by Calderón and Los empeños de una casa by Sor Juana) will be used to attempt to make visible how the central statements of the two dramas are expressed primarily at the level of language, even though non-linguistic means also play a major role. The two plays are compared because of their shared central philosophical questions and because of the available historical sources; in both cases, not only the two main texts exist, but also the accompanying pieces framing them.